2012
DOI: 10.1155/2012/820474
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in Dermoscopy to Minimize the Risk of Missing Melanoma

Abstract: During the last decades, induction of dermoscopy in the clinical setting resulted in significant modifications in the management of melanocytic lesions. Indeed, the dermatoscope reveals a fascinating world of morphologic structures invisible to the naked eye, adding valuable information to a clinician evaluating a mole. However, since the technique counts only a couple of decades, new research data are continuously gathering and modify the “optimal” management of melanocytic lesions. In the present paper, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
9
1
3
Order By: Relevance
“…Nodulani melanom lahko zato zamenjamo za benigne kožne tumorje, kot so vaskularni tumorji, dermalni in t. i. blue nevusi, dermatofibromi ter seboroične keratoze. 5 Nodularni melanom predstavlja le 10-15 % vseh melanomov, vendar kar 70 % tistih, ki so po Breslowu debelejši od 3 mm.6 Debelina po Breslowu je najpomembnejši napovedni dejavnik preživetja bolnikov z melanomom. 7 Najpomembnejši okoljski dejavnik tveganja za razvoj melanoma je intermitentna izpostavljenost ultravijoličnemu sevanju, vendar ta povezava ni značilna za nodularni podtip melanoma.8…”
Section: Uvodunclassified
See 2 more Smart Citations
“…Nodulani melanom lahko zato zamenjamo za benigne kožne tumorje, kot so vaskularni tumorji, dermalni in t. i. blue nevusi, dermatofibromi ter seboroične keratoze. 5 Nodularni melanom predstavlja le 10-15 % vseh melanomov, vendar kar 70 % tistih, ki so po Breslowu debelejši od 3 mm.6 Debelina po Breslowu je najpomembnejši napovedni dejavnik preživetja bolnikov z melanomom. 7 Najpomembnejši okoljski dejavnik tveganja za razvoj melanoma je intermitentna izpostavljenost ultravijoličnemu sevanju, vendar ta povezava ni značilna za nodularni podtip melanoma.8…”
Section: Uvodunclassified
“…Prav tako ga lahko zamenjamo z ostalimi malignimi kožnimi tumorji in celo z vnetnimi spremembami, še posebej, če ni pigmentiran. 5 Ker algoritem ABCDE pri nodularnemu melanomu odpove, so nekateri avtorji KLiNičNi PRiMER/CASE REPORT predlagali algoritem EFG (angl. elevation, firmnes, growth).…”
Section: Razpravljanjeunclassified
See 1 more Smart Citation
“…A ten-year multicenter study showed that the use of dermoscopy decreases the number of unnecessary excised benign melanocytic lesions and increases the number of detected melanomas. 4,5 of single melanocytic lesions, while medium (every 6 months) and long-term (every 12 months) follow up is focused on monitoring of multiple lesions. The lesions selected for shortterm follow-up usually fall into two categories: moderately atypical lesions without a history of change and mildly atypical nevi with a history of change.…”
Section: Dermoscopy (And Videodermoscopy)mentioning
confidence: 99%
“…These are: the pattern analysis by Pehamberger, the ABCD rule by Stolz, the ABC rule modified by Kittler, the Menzies method, the seven-point checklist by Argenziano, the CASH algorithm and other. 4,6,15,16 Figures 1 and 2 show typical dermoscopy features of thin versus thick melanomas. The images were taken with a digital dermoscope (videodermoscope).…”
Section: Dermoscopic Features In the Diagnosis Of Different Types Of mentioning
confidence: 99%